Perceptions of barriers towards reusable building material stores - Hess, Adam B., author; Nobe, Mary, advisor; Cotrell, Stuart, committee member; Clevenger, Caroline, committee member (Colorado State University. Libraries, 2013)
This paper explores perceptions of barriers towards reusable building material stores in Northern Colorado. Use of these stores minimizes harmful affects to the environment, creates affordable alternatives to new building materials, and benefits community by creating jobs. This study measures the attitudes of people as well as the perceived barriers associated with reusable building material stores. The model being used to test and measure these concepts is the Theory of Planned Behavior which states that behaviors are influenced by a person's attitude and their behavioral intentions. This paper applies part of the theory to see if attitudes and barriers predict behavioral intention. This information can help eliminate perceived barriers and increase attitudes therefore increasing the behavior of shopping at these reusable building material stores.
Keywords: attitude; barrier; behavior; materials; reusable; reuse